2014
DOI: 10.1016/j.sbspro.2014.01.406
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence in Building Interpersonal Communication Skills

Abstract: The aim of our paper is to identify the role of emotional intelligence in developing communication and relational skills. Evaluating the level of emotional intelligence is essential for building efficient communication, intellectual and emotional development. Socrate's advice "Know thyself!" finds its application in this case by (self)controlling one's emotions and adjusting them to the context, aiming at the need to know others and interact positively, skills that bring satisfaction and accomplishments to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 5 publications
2
42
0
7
Order By: Relevance
“…Our findings demonstrated an increase in the scores of general health domain of QoL following EI education. Likewise, Petrovici and Dobrescu (2014) in a study on 250 students in Romania reported that the EI education programme promoted individuals' QoL and health.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated an increase in the scores of general health domain of QoL following EI education. Likewise, Petrovici and Dobrescu (2014) in a study on 250 students in Romania reported that the EI education programme promoted individuals' QoL and health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emotions convey information and therefore function as communication signals, such as happiness is a signal of wanting to join with others or sadness is a signal of loss and wanting of comfort (Mayer et al 2008). Therefore, scholars have shed light on the relation between EI and communication competence, such as effective communication requires the management and recognition of one's own and others' emotional expression (Troth et al 2012a) or the ability to understand emotions contributes to developing communication skills (Petrovici and Dobrescu 2014). In a similar vein, George (2000) argued that in order to effectively communicate with other people about one own needs and concerns it is necessary to accurate appraise and express emotions of one's self and others'.…”
Section: Communication Competence In Agile Teamsmentioning
confidence: 99%
“…Meanwhile, the interpersonal skill is an inherent relationship based on the process of communication (1). Another research suggests a significant role of emotional intelligence in building interpersonal communication skill (2). Those who have high emotional intelligent also deem to have high score in performance (3).…”
Section: Interpersonal Communication Skillmentioning
confidence: 99%